Android-Based Expert Diagnosis System of Children’s Ear, Nose, and Throat Disorders Using Forward Chaining Method - Arlen Brilliannisa Hardiyanto; Susy Kuspambudi Andaini; Ramdhan Fazrianto Suwarman (LPPM Universitas Islam 45 Bekasi, 2024)
Ear, nose, and throat disorders are a significant health problem, especially in children. This article discusses the development of an expert system as a diagnosis tool for ENT disorders in children by applying the forward chaining method. The system development was carried out using the waterfall method and built based on android using Kodular. The system can diagnose 36 disorders with 42 symptoms obtained by literature study technique from the book First Aid in Your Home written by Dr Tony Smith and Dr Sue Davidson. The result of this system is able to help the process of diagnosing ENT disorders in children accurately based on knowledge from experts through android applications.